Respuesta :
Step-by-step explanation:
Simplifying
4x + -14 = 2x + 8
Reorder the terms:
-14 + 4x = 2x + 8
Reorder the terms:
-14 + 4x = 8 + 2x
Solving
-14 + 4x = 8 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
-14 + 4x + -2x = 8 + 2x + -2x
Combine like terms: 4x + -2x = 2x
-14 + 2x = 8 + 2x + -2x
Combine like terms: 2x + -2x = 0
-14 + 2x = 8 + 0
-14 + 2x = 8
Add '14' to each side of the equation.
-14 + 14 + 2x = 8 + 14
Combine like terms: -14 + 14 = 0
0 + 2x = 8 + 14
2x = 8 + 14
Combine like terms: 8 + 14 = 22
2x = 22
Divide each side by '2'.
x = 11
Simplifying
x = 11